A low‐profile dual‐polarized stacked patch antenna array with mutual coupling reduction for massive MIMO. Issue 8 (21st April 2021) - Tang, Xiaojun; Yu, Bin; Li, Yixin; Chen, Haidong
Abstract: In this article, a 2 × 2 stacked patch antenna array with low profile (0.047 λ 0 ) and compact size (the center to center distance of two subarrays is 0.5 λ 0 ) is presented. To reduce mutual coupling, a metal bar is disposed between the two subarrays. By investigating the current density distribution on the metal bar, the decoupling effect of the metal bar is explained. The proposed design is also fabricated and tested. The results show that operating bandwidth of 1.71 to 1.88 GHz is covered, with voltage standing wave ratio (VSWR) <1.4. The isolations between the co‐polarized ports and orthogonally‐polarized ports are higher than 27.5 and 27 dB, respectively. Stable radiation patterns are obtained over the operating frequency band. Due to the low mutual coupling between the adjacent elements, the half‐power beamwidth of the antenna array well converges.